Transition‐Metal‐Free Synthesis of N‐(1‐Alkenyl)imidazoles by Potassium Phosphate‐Promoted Addition Reaction of Alkynes to Imidazoles. Issue 1 (21st October 2013) - Lu, Linhua; Yan, Hong; Liu, Defu; Rong, Guangwei; Mao, Jincheng
Abstract The addition reaction of alkynes to N‐heterocycles by simply heating in DMSO with potassium phosphate is reported. Good yields with high stereoselectivity could be achieved for a range of substrates. The scope is quite general for both amines and phenylacetylenes. In addition, internal alkynes and α‐bromostyrene were also examined in this reaction. This process is efficient and useful for the synthesis of (Z)‐N‐(1‐alkenyl)imidazoles and related Z products. Thus, the reaction is useful because of the importance of the imidazole scaffold.